Sing the rage : listening to anger after mass violence - Chakravarti, Sonali (The University of Chicago Press, 2014)
What is the relationship between anger and justice, especially when so much of our moral education has taught us to value the impartial spectator, the cold distance of reason? In Sing the Rage, Sonali Chakravarti wrestles with this question through a careful look at the emotionally charged South African Truth and Reconciliation Commission, which from 1996 to 1998 saw, day after day, individuals taking the stand to speak-to cry, scream, and wail-about the atrocities of apartheid. Uncomfortable and surprising, these public emotional displays, she argues, proved to be of immense valu.